To assess the prevalence and factors determining timely initiation of breastfeeding among the mothers in resettlement colony in Delhi - Neelima, Thakur; Pragti, Chhabra; Dadhich, J P; Anita, Gupta; Vibharika, Chandola (Indian Journal of Child Health, 2016)
Background: The initiation of breastfeeding within 1 h of birth has various benefits and has been found to reduce neonatal mortality and morbidity. Objective: This study is designed to assess the prevalence and determinants of timely initiation of breastfeeding among mothers in a resettlement colony of Delhi. Materials and Methods: A community-based cross-sectional study was conducted in a resettlement colony of East Delhi among mothers with infants